'Soft power is such a benign animal': narrative power and the reification of concepts in Japan. Issue 4 (4th July 2019) - Winkler, Stephanie Christine
Abstract: The purpose of this article is to analyse how the seemingly natural fit between Japan and the soft power concept has been possible despite the notorious vagueness of the concept and what the consequences of soft power's reification are. By building on recent scholarship on concepts, expert knowledge and narratives, the article suggests that reification processes are best conceptualized as driven by concept coalitions. The article finds that soft power was narrated and nurtured into Japan's cultural diplomacy, Japan's relationship with the United States (US) and its security policy. The article, moreover, shows that the more soft power was understood, framed and accepted as benign and necessary, the more persuasive arguments about what Japan should do or be in order to wield soft power became. This has legitimized narratives that suggest that Japan's 'proactive contribution to peace' as a responsible ally of the US constitutes an inevitable source of soft power.